Precipitation forecasting using multilayer neuralNetwork and support vector machine optimization based on flow regime algorithm taking intoAccount uncertainties of soft computing models - Banadkooki F.B.; Ehteram M.; Ahmed A.N.; Fai C.M.; Afan H.A.; Ridwam W.M.; Sefelnasr A.; El-Shafie A. (MDPI, 2023)
artificial neural network; decision making; interpolation; numerical model; optimization; performance assessment; precipitation intensity; principal component analysis; support vector machine; water resource; Iran